2014
DOI: 10.1002/ccd.25644
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage closure using the amulet device: An initial experience with the second generation amplatzer cardiac plug

Abstract: The Amulet device, which has new novel features as compared with the first generation ACP, is a feasible option for LAA closure. From our initial experience, implantation of the Amulet is associated with high success rate and good short-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…Lam et al . detected 2 leaks <2 mm, which are likely clinically irrelevant using the second generation Amplatzer TM cardiac plug . Two patients in our study presented a thrombus at the device.…”
Section: Discussionmentioning
confidence: 58%
“…Lam et al . detected 2 leaks <2 mm, which are likely clinically irrelevant using the second generation Amplatzer TM cardiac plug . Two patients in our study presented a thrombus at the device.…”
Section: Discussionmentioning
confidence: 58%
“…These series with 17 [7], 20 [8], 24 [9] and 50 [10] patients reported 100%, 100%, 96% and 94% procedural process. The Amulet observational study with 1,073 patients reported 98.8% implant success [14].…”
Section: Discussionmentioning
confidence: 91%
“…First series of LAAO with the Amplatzer Amulet showed similar procedural and short-term clinical outcomes compared with the ACP [7][8][9][10]. In the series of Abualsaud et al [11] with 50 patients the Amulet was associated with a significant reduction in residual leaks at follow-up.…”
Section: Introductionmentioning
confidence: 90%
“…The Watchman FLX can be partially recaptured into the access sheath, re-maneuvered and repositioned either proximally, like the previous generation device, or advanced distally several times before device release due to atraumatic closed distal end using the “ball technique” which helps to find the ideal placement – this technique, quite new for Watchman operators, is well known for Amplatzer Cardiac Plug and Amplatzer Amulet left atrial appendage occluder (St. Jude Medical) implanters [6]. Full recapture is also allowed at every stage of the procedure before the final release of the device.…”
Section: Device Descriptionmentioning
confidence: 99%